Hope Sebagai Mediator Pengaruh Authentic Leadership Terhadap Work Engagement Pada Anggota Polisi - Kurniawati, Rizka; Latipun, Latipun; Hasanati, Nida (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2023)
Abstract : The work engagement of Indonesian National Police can provide a good performance to organization. One of the factors that can improve hope towards work engagement of Indonesian National Police is the style of leadership. Therefore, aiming to identify the influence of authentic leadership over work engagement, this study applies hope as the mediator variable. Using non-experimental quantitative as the research design, the subject involves 163 members of Sabhara Division of Indonesian National Police performing purposive sampling. The instrument of work engagement data collection is measured using Utrecht Work Engagement Scale (UWES-17), authentic leadership using Authentic Leadership Questionnaire (ALQ), and hope using the Adult State Hope Scale (ASHS). The data is analyzed using Mediated Regression Analysis (MRA) process by Hayes. The result shows that (1) authentic leadership positively impacts on work engagement, (2) authentic leadership positively impacts on hope, (3) hope positively impacts on work engagement, and (4) hope performs as the mediator of the influence of authentic leadership on work engagement. Keywords: authentic leadership, hope, work engagement. Abstrak : Work engagement anggota Polri dapat memberikan performa organisai yang lebih baik. Gaya kepemimpinan di organisasi merupakan faktor yang meningkatkan hope terhadap work engagement anggota Polri. Penelitian ini bertujuan untuk menguji pengaruh antara authentic leadership terhadap work engagement dengan hope sebagai variabel meditor. Desain penelitian menggunakan pendekatan kuantitatif non eksperimental. Subjek penelitian ini adalah anggota Polri Divisi Sabhara berjumlah 163 anggota kepolisian, dengan menggunakan teknik purposive sampling. Instrumen pengumpulan data work engagement diukur menggunakan Utrecht Work Engagement Scale (UWES-17), authentic leadership diukur menggunakan Authentic Leadership Questionnaire (ALQ), dan hope diukur menggunakan The Adult State Hope Scale (ASHS). Data dianalisis menggunakan Mediated Regression Analysis (MRA) process oleh Hayes. Hasil penelitian yang didapatkan (1) authentic leadership berpengaruh positif terhadap work engagement (2) authentic leadership berpengaruh positif terhadap hope (3) hope berpengaruh positif terhadap work engagement (4) hope berperan sebagai mediator pengaruh authentic leadership terhadap work engagement. Kata kunci : authentic leadership, hope, work engagement.